Costos como medio de proyección de la producción orgánica de hortalizas como: cebolla blanca, pimiento, cilantro y lechuga en el Colegio Pueblo Nuevo de la Parroquia La Guayas, año 2014. - Ruiz Macías, Dolores Maribel (2015)
This research was conducted at school, "New Village". The Guayas parish 10km from right outside El Empalme Canton, Guayas Province. This study focuses on organic agriculture as an alternative to promote diversification of the production of small farmers. Organic production consisted in the replacement of synthetic chemical inputs agronomic, biological and mechanical practice. The aim of this study was to determine the costs, profitability and breakeven get organic vegetables produced in the school "Pueblo Nuevo" The Guayas parish. The determination of costs arises as a logical consequence of the expenses and costs arising in the production of vegetables in total and unit terms, the amount of monetary resources required by this job in your life. Production costs, cost management, sales and financial costs: In all work as production costs are distinguished. Costs generated in crops were structured according to input costs for planting vegetables, labor, depreciation, net profits to bring profitability and production costs per hectare. Giving best result growing white onion having a volume favorable production in treatment 3, while in treatment 2 the lowest cost in the same culture was generated by that raises the yield to having a lower volume of production treatment 3